A COMPARATIVE STUDY OF RETAIL IMAGE ON SHOPPING CENTERS IN MANADO (CASE STUDY OF CONSUMERS IN MANADO TOWN SQUARE AND MEGA MALL MANADO) - Claudia, Pantow Nancy (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT Â  Recently, everyone starts to follow thet trend and it makes people wants to fulfill their desire. People began to find places for their various activities or for their leisure time with friends, family, even to purchase their persona needs. Most of them go to malls as their lifestyle. This research try to observe retail image captured by the consumers, with a variable which are: store location, merchandise, price, service, and physical facilities. Situational factors are a useful tool in analyzing the impact of situational variables on purchasing outcomes since it includes variables that might be controlled by retailers. 100 repondents or consumers whose ever visit Manado Town Square and Mega Mall Manado as a sample of this study. This research concludes that from those five elements of retail image, there are few significant differences of consumerâ€™s valuation image for Manado Town Square and Mega Mall Manado especially for the price and customer service. Keywords: shopping centers, retail image